A randomized comparison of long acting methylphenidate and cognitive behavioral therapy in the treatment of binge eating disorder. (March 2019) - Quilty, Lena C.; Allen, Timothy A.; Davis, Caroline; Knyahnytska, Yuliya; Kaplan, Allan S.
Highlights: Both long acting methylphenidate and cognitive behavioral therapy were associated with significant improvement in clinical outcomes in adult women with binge eating disorder. Methylphenidate was associated with greater decrease in body mass index over treatment than CBT; however, the durability of these effects is unknown. Two traits of impulsivity were predictive of clinical outcomes. Abstract: Cognitive behavioral therapy (CBT) is a well-established treatment for binge eating disorder (BED); however, this treatment is underutilized, highlighting the need for additional treatment alternatives. Dopamine neurotransmission has been associated with dysregulated eating, and pharmaceutical agents targeting the dopamine system are associated with decreased binge eating and weight. The primary objective of the current investigation was to evaluate the efficacy of psychostimulant medication versus current best practices in the treatment of BED symptoms, in a randomized trial of methylphenidate versus CBT for BED. The secondary objective was to evaluate the ability of impulsivity to predict treatment outcomes. Female outpatients with BED were randomized to receive methylphenidate ( n  = 22) or CBT ( n  = 27) for 12 weeks. The primary outcome was objective binge episode frequency; secondary outcomes included subjective binge episode frequency, body mass index (BMI), BED symptoms, and quality of life. Results showed that both treatments had a significant impact on primary and secondary outcomes. Methylphenidate and CBT were associated with decreases in subjective and objective binge episodes; methylphenidate was associated with greater decreases in BMI. Two impulsivity traits predicted clinical outcomes. Results provide preliminary support for the therapeutic benefit of methylphenidate in BED treatment, and prognostic utility of impulsivity in this context.